Women in computer science careers - Kahn, Jetty (Mankato, Mn. : Capstone Press, 2000)
Describes the careers of five women working in the computer science field: Maria Gini, Jessica Hodgins, Fern Hunt, Bonnie Labosky, and Misha Mahowald.
Includes bibliographical references (p. 45) and index.
Keywords: Computer science -- Vocational guidance -- Juvenile literature; Computers and women -- Juvenile literature; Computer scientists; Women -- Biography